Methodology for defining the effects of outdoor air pollution on children's health at the population level - Galičič, An (Sanitarno inženirstvo, 2015)
Outdoor air pollution is an important determinant of health. Children are one of the most sensitive population groups due to their yet underdeveloped respiratory system. Methodology for linkage environmental and health data at population level had been initiated by the World Health Organization about twenty years ago. The aim of our study is an overview of methods with which the effects of outdoor air pollution on children's health have been investigated at the population level. Literature overview was made systematically. Health effects of outdoor air pollution at the population level were firstly investigated after 1990. Simultaneously with the most common outdoor air pollutants (NO2, SO2, O3, PM10 and CO) monitoring of health effects was measured. Poisson regression analysis was the most frequently used method of ecological timeseries studies and spatial studies. Exposure misclassification was in this research field the most common limitation of ecological studies. This study supports the need of future research on outdoor air pollution's effects on the at population level from an engineering and public health view.
Keywords: onesnažen zrak; outdoor air pollution; children health; zdravje otrok; škodljivi učinki; time-series study; spatial study; methodology